Reliability of oral biomarkers in the prediction and diagnosis of periodontal disease / Zeyad Nazar Majeed - Zeyad Nazar , Majeed (2017)
Introduction: Research has been intense in investigating the possibility of using the ideal oral fluids in the prediction and diagnosis of periodontal disease. In the last few decades, there has been a growing trend to develop better methods to monitor periodontal disease. Objectives: The aim of this study was to compare and correlate between the microbiological findings and levels of oral biomarkers at different periodontal disease stages among the three ethnic groups of the Malaysian population. This study is aimed to detect the most accurate biomarkers that can be used to predict and diagnose periodontal disease in these populations. Methods: Gingival crevicular fluid (GCF) and subgingival plaque samples from 28 healthy subjects (H), 30 patients with generalized gingivitis (G) and 30 patients with moderate to severe chronic periodontitis (CP) were collected. The levels of biomarkers (LL-37, MMP-8, MMP-9, IL-6, IL-1β, TNF-α, OPG, OC and PGE2) were quantified by enzyme-linked immunosorbent assay (ELISA) while the subgingival periodontal pathogens (Tannerella forsythia, Treponema denticola, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans ) were identified using Real Time-polymerase chain reaction (RT-PCR). Cumulative Risk Score (CRS), a new statistical approach, was used to evaluate the accuracy of applying oral biomarkers in the diagnosis of periodontal disease based on three selected biomarkers. Results: The results of this study indicated that the ethnic backgrounds of the subjects had no noticeable effect on the periodontal pathogens count and the expression of a majority of oral biomarkers during the progression of periodontal disease. However, only LL-37 levels among the selected biomarkers showed significant difference between the ethnic groups (p<0.05). Each biomarker was associated with periodontal disease in the different stages of disease progression. The results of this study showed that MMP-8, IL-1β, PGE2 and IL-6 in GCF are associated with increased count of periodontal pathogens and different clinical periodontal parameters when compared to the other biomarkers. This association increased significantly by using CRS, which had 2 to 3 times higher odds ratios than the use of any selected biomarkers alone. The area under the curve (AUC) values also increased from 0.653–0.704 for the selected biomarkers separately up to 0.749 for the three selected biomarkers cumulatively represented by CRS. Conclusions: In conclusion, this study showed that the levels of biomarkers in the GCF mainly MMP-8, IL-1β, PGE2 and IL-6, if used separately, could be useful in the prediction and diagnosis of periodontal disease to a certain degree of accuracy. The study also showed that the combination of three GCF biomarkers in a single biomarker package to establish the CRS index is more precise in the prediction and diagnosis of periodontal disease than the use of other biomarkers.